Elevated CA19‐9 Is Associated With Increased Mortality In A Prospective Cohort Of Hepatocellular Carcinoma Patients. Issue 2 (February 2015) - Hsu, Christine C; Goyal, Abhishek; Iuga, Alina; Krishnamoorthy, Saravanan; Lee, Valerie; Verna, Elizabeth C; Wang, Shuang; Chen, Fei‐Na; Rodriguez, Rosa; Emond, Jean; Berk, Paul; Lefkowitch, Jay; et al.
Abstract : OBJECTIVES: : Hepatocellular carcinoma (HCC) is the third leading cause of cancer‐related deaths worldwide. CA19‐9 is a glycoprotein that predicts poor prognosis in pancreatic and biliary malignancies. We evaluated it as a prognostic biomarker for patients with HCC. METHODS: : We prospectively enrolled 145 patients with HCC, diagnosed using American Association for Study of Liver Diseases criteria, between October 2008 and November 2012. We examined whether baseline serum CA19‐9 levels predicted overall survival. We also examined immunostains of hepatic resections and explants of patients with elevated and normal serum CA19‐9. RESULTS: : In a cohort of predominantly hepatitis C and B patients, CA19‐9 ≥100 U/ml was associated with a 2.7‐fold increased mortality (hazard ratio (HR): 2.72; 95% confidence interval (CI): 1.52–4.88, P <0.001). It remained a significant predictor (HR: 2.58; 95% CI: 1.41–4.72, P =0.002) in a multivariable model adjusted for Child–Pugh score, alpha‐fetoprotein, Barcelona Clinic Liver Cancer stage, and Model for End‐Stage Liver Disease. CA19‐9 immunohistochemistry performed on a subset of liver resection and explant specimens showed increased CA19‐9 immunostaining of non‐tumor liver parenchyma in patients with elevated serum CA19‐9. It also showed staining of native and reactive bile ducts, and of progenitor‐like cells at the periphery of cirrhotic nodules. CONCLUSIONS: : Elevated serum CA19‐9 ≥100 U/ml is an independent predictor of poor overall survival in this hypothesis‐generating study. The unfavorable prognosis seen with elevated serum levels may be related to progenitor‐like cells in the non‐tumor liver.